(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to determine the effect of replacing FM with mealworm (Tenebrio molitor) on the growth performance and immunologic responses of white shrimp. In addition, the toxicity of such replacement to white shrimp was measured. Mealworm was incorporated to partially or totally replace fish meal in diets for white shrimp. Experimental groups of shrimp with an average initial body weight of 2.39 ± 0.49 g were fed each of 4 isonitrogeneous diets formulated to include 0, 25, 50 and 100% (control, MW25, MW50 and MW100 respectively) of mealworm substituted for fish meal. After eight weeks of feeding trials, shrimp fed diets MW25, MW50 and MW100 had higher live weight gain (10.05 ± 3.06, 11.41 ± 2.08, and 10.36 ± 1.57, respectively), higher specific growth rate (2.56 ± 0.11, 2.79 ± 0.09, and 2.61 ± 0.07, respectively), and better feed conversion ratio (2.89 ± 0.08, 2.69 ± 0.09, and 2.72 ± 0.19, respectively) compared to those of shrimp fed control diet. Survival rate was 98% in all treatments. No toxicity was found in post-mortem pathophysiologic examinations. The levels of immune markers such as beta-glucan binding protein, prophenoloxidase and crustin associated with shrimp’s cellular and humoral immunity were found to be higher in 25 and 50% mealworm replacement groups. These results clearly indicated that replacement of fish meal with 50% mealworm for shrimp diet was optimal in promoting the growth performance of shrimp without any adverse effect.